Improving Allocative Efficiency in Zimbabwe’s Health Sector : Results from the Health Interventions Prioritization Tool - Hou, Xiaohui; Jaoude, Gerard Abou; Gosce, Lara; Shamu, Shepherd; Sisimayi, Chenjerai N.; Lannes, Laurence; Wilkinson, Thomas David; Kerr, Cliff; Haghparast-Bidgoli, Hassan; Skordis, Jolene (World Bank, Washington, DC, 2021)
The country of Zimbabwe has seen some important improvements in key health outcomes since 2009. However, despite progress in some areas of the health sector, the country did not meet its Millennium Development Goals (MDGs) and current progress falls short of the Sustainable Development Goals (SDGs) milestones. As is often the case, the poor and rural populations in Zimbabwe bear a disproportionate burden of disease and health risks. The situation is compounded by national economic challenges and health sector spending inefficiencies that have resulted in households bearing an increasing share of health sector financing, mainly through out-of-pocket expenditures. Households provide approximately 25 percent of health sector financing in Zimbabwe. Again, the poor and rural populations are hardest hit by this economic reality. Zimbabwe was one of the few countries in which HIPtool was piloted at the proof of concept stage. HIPtool enables the mathematical prioritization of interventions based on existing data and a set of criteria. It provides a technical foundation to further develop an essential health benefits package. However, HIPtool, at this stage in development, still has strong limitations, which are outlined along with results in this report.